Cleptobiosis in Social Insects - Michael D. Breed; Chelsea Cook; Michelle O. Krasnec (Psyche: A Journal of Entomology)
In this review of cleptobiosis, we not only focus on social insects, but also consider broader issues and concepts relating to the theft of food among animals. Cleptobiosis occurs when members of a species steal food, or sometimes nesting materials or other items of value, either from members of the same or a different species. This simple definition is not universally used, and there is some terminological confusion among cleptobiosis, cleptoparasitism, brood parasitism, and inquilinism. We first discuss the definitions of these terms and the confusion that arises from varying usage of the words. We consider that cleptobiosis usually is derived evolutionarily from established foraging behaviors. Cleptobionts can succeed by deception or by force, and we review the literature on cleptobiosis by deception or force in social insects. We focus on the best known examples of cleptobiosis, the ectatommine ant Ectatomma ruidum, the harvester ant Messor capitatus, and the stingless bee Lestrimellita limão. Cleptobiosis is facilitated either by deception or physical force, and we discuss both mechanisms. Part of this discussion is an analysis of the ecological implications (competition by interference) and the evolutionary effects of cleptobiosis. We conclude with a comment on how cleptobiosis can increase the risk of disease or parasite spread among colonies of social insects.